Checklist of land snail species of Gua Rumbang, Sarawak, Malaysian Borneo (Mollusca, Gastropoda), with a description of a new species, Diplommatina rumbangensis sp. nov. - Nurul Syafiqah, Nasir; Lee, Jie Ying; Mohammad Effendi, Marzuki; Jaap J., Vermeulen; Mohd Azlan, Jayasilan; Mohd Zacaery, Khalik (Pensoft Publishers, 2024)
The current study presents an annotated checklist of the land snail species in the vicinity of the limestone hill of Gua (= cave) Rumbang, an outcrop located at the district of Padawan, Sarawak, Malaysian Borneo. The sampling was conducted at the surrounding areas and near the cave’s entrance. A total of 62 species, involving 19 families and 38 genera, were recorded. Comparison with previous surveys made in the Bau limestone hills revealed similarities with respect to the species-rich families Diplommatinidae and Cyclophoridae, and the genera Kaliella and Diplommatina, highlighting the regional consistency of the land snail diversity of the Bau-Padawan-Serian cluster. Possibly because of its smaller size, Gua Rumbang is home to two endemic species, while there are eight endemic species in the Bau limestone karsts. This suggests a potential for a significant species diversity within the areas of the limestone ranges that remain to be explored. Nonetheless, the occurrence of endemic species in Gua Rumbang highlights the need to conserve certain areas within the Padawan limestone range since hitherto no protected areas have been proposed in this region. In this checklist, a new species for science is also described, namely, Diplommatina rumbangensis sp. nov.